E-MODUL INTERAKTIF BERORIENTASI VAK CONTENT MATA PELAJARAN KOMUNIKASI DATA - Mertayasa, I Nengah Eka (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2019)
This research aims to determine the design and implementation of the e-module in VAK (visual auditory kinaesthetic) content in Class XI students of TKJ program in SMK Negeri 3 Singaraja which is one of the solutions for Improve student learning achievements. The research method used is the development method of AM3PU3. Subjects in this study are learning content experts, learning media experts, learning design experts, individual students, small group students, and students in field trials. The variables examined in this study are e-modules of VAK content and student learning achievements. Research Data is collected using oral interview instruments, questionnaire, and study achievement tests. The results of the research Data were analyzed descriptively qualitative, quantitative descriptive, and inferential (t-test) statistics. Data analysis results show that it has been successfully designed an e-module of VAK content for data communication learning and has been valid for use. Results of inferential statistical analysis showed that the e-module of VAK contentare effective for enhancing students' learning achievements.